2019
DOI: 10.1177/0361198119850464
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Two-Regime Stochastic Car-Following Model: Explaining Capacity Drop and Oscillation Instabilities

Abstract: The Standing Committee on Traffic Flow Theory and Characteristics (AHB45) peer-reviewed this paper (19-05914).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…In the authors' previous work (10), it was found that if we select m ' 1:2, then the model could replicate both the oscillation and capacity drop. However, the present analysis with the NGSIM data gives a strong indication that the value of m is larger than 3, which means that the acceleration processes of drivers are closer to a Brownian motion than to a geometric Brownian motion.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the authors' previous work (10), it was found that if we select m ' 1:2, then the model could replicate both the oscillation and capacity drop. However, the present analysis with the NGSIM data gives a strong indication that the value of m is larger than 3, which means that the acceleration processes of drivers are closer to a Brownian motion than to a geometric Brownian motion.…”
Section: Discussionmentioning
confidence: 93%
“…The model used in this paper is the two-regime stochastic car-following model of Xu and Laval (9,10). It corresponds to an extension of Newell's simplified 1 Georgia Tech, Atlanta, GA car-following theory (11), where vehicle location is given by the minimum of a free-flow term expressing the location (Y ) that the vehicle can achieve when unobstructed by traffic, and a congestion term giving the most downstream location (Z) that the vehicle can safely achieve without colliding with its leader.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably the simplest CF model that captures driver random errors while accelerating and produces realistic traffic oscillations. Follow-up models that incorporate human error have also been formulated within this family (142,143) and also for other well-known CF models (144).…”
Section: Randomnessmentioning
confidence: 99%
“…Laval et al (2014) introduced white noise into the Newell model, which then enables the model to reproduce the formation of oscillations. Later, Yuan et al (2018) and Xu and Laval (2019) further improve the model by Laval et al (2014).…”
Section: Introductionmentioning
confidence: 99%